Exploring the Impacts of Economic Growth, Population and Economic Crisis on Public Education Expenditure in Malaysia - Wong Sing Yun; Janice L.H.Nga (Society of Cultural Studies and Social Sciences, 2023)
This paper intends to fill the literature gap by empirically examines the relationship between public education expenditure, economic growth, demography size and economic crisis in Malaysia. Model formulated based on Wagner’s law concept, with focus on the effect of economic crisis and population size will be employed. The results supported Wagner's law and demonstrated significance of both population size and economic crisis in determining the public education expenditure. This paper will further contribute useful insight to policymakers to consider the effects’ of the demographic variable, economic growth and crisis’ impact when making any public education spending policy decision. Keywords: Public Education Expenditure, Economic Growth, Population, Crisis, Malaysia